2021
DOI: 10.1016/j.jcmg.2019.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Intima-Media Thickness in the Young

Abstract: Objectives This study characterized the determinants of carotid intima-media thickness (cIMT) in a large (n > 4,000) longitudinal cohort of healthy young people age 9 to 21 years. Background Greater cIMT is commonly used in the young as a marker of subclinical atherosclerosis, but its evolution at this age is still poorly understood. Methods Associations between cardiovascular risk factors and cIMT were investigated in both longitudinal (ages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
99
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(107 citation statements)
references
References 29 publications
7
99
1
Order By: Relevance
“…Corresponding, a significantly higher tensile stress was found in obese and overweight girls and boys in this study population. Similar results were made by Chiesa et al [29], who described an increased lumen, but a lower IMT with a reduced IDR and an increased tensile stress in obese young study participants. These findings indicate that risk factors for CVD, such as obesity, may be better explained by referring to IDR than IMT alone.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Corresponding, a significantly higher tensile stress was found in obese and overweight girls and boys in this study population. Similar results were made by Chiesa et al [29], who described an increased lumen, but a lower IMT with a reduced IDR and an increased tensile stress in obese young study participants. These findings indicate that risk factors for CVD, such as obesity, may be better explained by referring to IDR than IMT alone.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the values of this healthy study population, a constant IDR over childhood can be assumed. In concordance, Chiesa et al [29] suggested that increased fat-free mass is the predominant factor leading to a thickened IMT. In a growth-associated physiologic process, D increases as well-IDR, thereby, is kept at a constant level.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Unexpectedly, we found CRP in ALSPAC to in fact be negatively associated with a number of risk factors in fully-adjusted models, and was therefore associated with a decreased risk of MetS during follow-up. The reasons for this are unclear, but are similar to previous findings in this same cohort where CRP has shown some evidence of a negative relationship to carotid intima-media thickness -a commonly-used marker of subclinical atherosclerosis (30).…”
Section: Discussionsupporting
confidence: 81%